Sudoku-based health improves Gen Z’s knowledge and attitudes toward adolescent pregnancy risks - Intan Nugraheni Hasanah; Sri Setiasih; Triana Sri Hardjanti; Cinta Kasih Salsabilla (Poltekkes Kemenkes Yogyakarta, 2026)
Adolescent pregnancy remains a public health concern in many countries, including Indonesia, as it increases the risk of maternal and infant mortality. Limited knowledge and inappropriate attitudes are contributing factors. This study explores the use of Sudoku games as an innovative medium for health education, aimed at enhancing student engagement and promoting interactive learning. The objective is to assess the effect of health education through Sudoku games on the knowledge and attitudes of Generation Z regarding adolescent pregnancy. This study employed a quantitative method with a pre-experimental design, utilizing a one-group pretest–posttest approach. The population consisted of 160 students, with a sample of 60 eleventh-grade students from Pembangunan Nasional Vocational School, Purwodadi. Samples were selected using purposive sampling, and the sample size was determined using the Slovin formula with a 5% margin of error. The intervention was conducted over one day, and data were analyzed using the Wilcoxon test. The results of this study indicate a significant effect. The proportion of students categorized as having good knowledge increased from 1.7% to 100%, representing a 98.3 percentage-point increase, with a significant effect (Z = -6.743, p < 0.001, r = -0.87). Attitude scores also improved from 33.3% to 88.3%, reflecting a 55 percentage-point improvement, indicating a shift toward more positive attitudes about the risks ofadolescent pregnancy (Z = -6.548, p < 0.001, r = -6.548). Both outcomes demonstrated medium-to-large effect sizes, confirming the educational relevance of the intervention. The provision of health education through Sudoku as an instructional medium demonstrated a significant influence on the knowledge and attitudes of Generation Z (Gen Z) concerning the risks ofadolescent pregnancy. These findings indicate that the Sudoku game can be utilized as an effective and practical tool for adolescent reproductive health education and holds potential as a reference for future scholarly investigations.